Faktor Penghambat Pemuridan Pemuda Gereja Pada Program Sekolah Minggu Kaum Muda Gereja Baptis di Kota Yogyakarta - bobby hartono hartono (STT INTI Bandung, 2022)
The youth are the next generation whom doing church services in the future. The growth of youth either quality or quantity needs church concern. For example, the youth discipleship program through the youth Sunday school program at Indonesian Baptist churches, especially in the city of Yogyakarta in particular and in Indonesia in general, was carried out as an effort by the church to prevent the decline in the presence of young people in fellowship and discipleship by way of maturation of faith.Although it’s been done, but it hasn’t shown any results. In this thesis author wants to research further how to developing deep faith for youth, through Youth Sunday School. We will focus on indicator is obstacles in Youth Sunday School of Indonesian Baptist Church in Yogyakarta. The research samples involved the respondents of Sunday School administrators and the pastor of the Indonesian Baptist Church in Yogyakarta. The qualitative data analysis process includes three sub-processes. It’s consist of description, analysis, and interpretation. The research said the obstacles was found that there are couples of factor, there are Individual factor, Family factor, and another factor from inside and outside of the church.